A memória na construção da protagonista em memorial de Maria Moura de Rachel de Queiroz - Santana, Ana ângela de Oliveira (2013)
The present research aims to analyze the novel Memorial de Maria Moura focusing on memory in the construction of the protagonist. The approach is supported by the works of Le Goff, Maurice Halbwachs and Michel Pollak, expanding to gender studies. The starting point is the assumption that the protagonist becomes subject of her own story through her family memories. Our conclusion is that Maria Moura, valorizing her family memories empowers herself, understands her family history and becomes able to be herself, that is, she represents one among the multiplicity of her family memories.